On Thermodynamics and Kinetics of Interface‐Induced Crystallization in Polymers. Issue 8 (9th February 2023) - Dolynchuk, Oleksandr; Thurn‐Albrecht, Thomas
Abstract: Crystallization initiated at interfaces is a ubiquitous phenomenon, covering both simple liquids and polymer melts. Understanding the physical process underlying interface‐induced crystallization in polymers is of fundamental interest and is relevant for many applications, especially for films of functional semicrystalline polymers. Interface‐induced crystallization of liquids can proceed either by heterogeneous nucleation or by the less explored equilibrium phenomenon of prefreezing. This study reports recent progress in the theoretical and experimental investigation of the effect of substrate‐material interactions on the thermodynamic properties of prefreezing and on the kinetics of heterogeneous nucleation in model polymers on different flat substrates. Through a combination of various microscopy and scattering techniques, supported by theoretical analysis, a detailed picture of the two different phenomena of interface‐induced crystallization in polymers is achieved. Abstract : This perspective discusses recent achievements in the theoretical and experimental investigation of two phenomena of interface‐induced crystallization in polymers – prefreezing and heterogeneous nucleation. Special attention is paid to the influence of substrate‐material interactions on crystallization temperature, crystal orientation, and semicrystalline morphology.